HUBUNGAN SUDUT Q-ANGLE TERHADAP FUNGSIONAL KNEE PADA KASUS PATELLOFEMORAL PAIN SYNDROME (Lembaga Penerbitan Universitas Esa Unggul, 2019)
AbstractAim: Determine the relationship between Q-angle with knee function in patellofemoral pain syndrome (PFPS) aged 16-19 years old. Method: This research is a non-experimental research in the form of a correlation study to analyze the relationship Q-angle is related to functional knee. A total of 25 students (16-19 years old) from SMA Yadika 3, Karang Tengah. The measuring instrument used a goniometer for the degree of the Q-angle and the Knee Injury and Osteoarthritis Outcome Score (KOOS) for the measurement a functional knee. Results: Correlation test with the Spearment Rank Correlation Test showed a not significant score of p=0.454 (p>0.05) with r= -0.157. Average and standard deviation of degree of the Q-angle is 18.40 ± 2.18 and of the functional knee is 59.26 ± 10.81. Conclusion: There is no correlation between Q-angle and functional knee in Patellofemoral Pain Syndrome. Keywords: Q-angle, functional knee, KOOS (knee injury and osteoarthritis score) AbstrakTujuan: Mengetahui hubungan sudut Q-angle terhadap Fungsional Knee pada kasus Patellofemoral Pain Syndrome yang berusia 16-19 tahun. Metode: Penelitian ini merupakan penelitian non eksperimental berupa studi korelasi untuk menganalisis hubungan sudut Q-angle terhadap Fungsional knee. Total sampel sebanyak 25 orang siswa/siswi yang berusia 16-19 tahun yang merupakan siswa/siswi Sekolah Menengah Atas Yadika 3, Karang Tengah. Alat ukur yang digunakan adalah Goniometri untuk Sudut Q-angle dan Knee Injury and Osteorthritis Outcome Score (KOOS) untuk Fungsional Knee. Hasil: Uji korelasi dengan Pearson Correlation Test didapatkan nilai tidak signifikan p= 0,503 (p>0,05) dengan r= -0,140 Rata-Rata dan standar deviasi Sudut Q-angle sebesar 18,40 ± 2,48 dan pada Fungsional knee 59,26 ± 10,81. Kesimpulan: Tidak terdapat hubungan sudut Q-angle terhadap fungsional lutut pada kasus Patellofemoral Pain Syndrome Kata kunci: Sudut Q-angle, fungsional lutut, KOOS (Knee Injury and Osteorthritis Score)